Critical Discourse Analysis of “Criticism of the Representation of Islam in Western Media and the Role of Da’wah in Transformation” by Suud Sarim Karimullah - Rahman, Fathan Tibyan; Sajidin , Sajidin (Jurnal Iman dan Spiritualitas, 2026)
This study critically analyzes Suud Sarim Karimullah's article, "Criticism of the Representation of Islam in Western Media and the Role of Da'wah in Transformation," using Norman Fairclough's three-dimensional Critical Discourse Analysis (CDA) model (text, discursive practice, social practice). It examines the article's discursive construction, legitimation strategies, and ideological tensions, including binary oppositions between "Western media" and "Islam," da'wah as dialogical "soft resistance," reverse essentialism, discursive hybridity, and the postcolonial intellectual's subject position. Through close reading of lexical choices, arguments, intertextuality, and social functions, the analysis reveals the text's sermonic-academic hybridity and its universalizing Islamic epistemology as a counter-hegemonic response. Findings urge da'wah practitioners to avoid reverse essentialism, embrace internal diversity in counter-narratives, and integrate critical reflexivity into media literacy education. This reflexive CDA application contributes to Islamic media studies and postcolonial discourse by illuminating paradoxes in counter-hegemonic knowledge production.